Development of halal verification and tracking system for halal-certified restaurants in Brunei Darussalam using augmented reality technology - Pg Hj Metussin, Ak Mohd Syukri (2015)
The government of Brunei Darussalam is putting in efforts to ensure that every Muslim regardless whether they are citizens or tourists to be well informed on ‘Hallalan Toyyiban’ food and beverages because consuming ‘halal’ food is a priority for all Muslims. However, due to the abuse of fake ‘halal’ certificates, limited numbers of ‘halal’ certified restaurants in Brunei Darussalam and non-availability of proper systems to locate ‘halal’ certified restaurants, Muslims in Brunei Darussalam are facing difficulties in finding genuinely ‘halal’ certified restaurants. Therefore, a study was conducted with a primary objective to identify ‘halal’ certified restaurants in Brunei Darussalam and to develop a prototype of ‘halal’ Verification System using Augmented Reality (AR) Technology for ‘halal’ certified restaurants in Brunei Darussalam. A list of ‘halal’ certified restaurants is obtained from Brunei Halal Food Council which serves as a guideline for conducting observation to collect coordinates and questionnaire survey on every ‘halal’ certified restaurant in Brunei Darussalam. Augmented Reality (AR) feature within Android environment were designed and developed using Android Software Development Kit. “Salam Halal” was the name given to the smartphone application that functions mainly to identify ‘halal’ certified restaurants within user current location. Informative, user friendly and interactivity are the main features of the application. Prior to “Salam Halal” development, a field survey and a quantitative study were conducted with 108 ‘halal’ certified restaurant’s owners and managers to identify ‘halal’ restaurants and to understand their perception of having ‘halal’ certificates for their ‘halal’ restaurants businesses. Once the application development was completed, 10 out of the 108 respondents were selected to as samples to further study perception towards “Salam Halal”, its effectiveness and how it can help in promoting their ‘halal’ restaurants. Statistical analysis using “Precision and Recall” methods were used to analyze the data. All tests using the prototype’s application was proven to be successful with the respondents able to locate the nearest ‘halal’ certified restaurants and they admitted that AR technology can be very helpful in promoting ‘halal’ restaurants. This compliment Brunei Darussalam’s image as an Islamic country while promoting the guidelines of Islamic hygienic food preparation.